The effects of environmental enrichment on biochemical and metric parameters of aged rats - Vieira, Thiago Aparecido; Carvalho, Rodrigo Leal de Paiva; Ferreira, Sarah Cristina; Oliveira, Ana Paula de; Modesto Junior, Olayr; Assis, Welton Ferreira de [UNESP]; Leme, José Alexandre Curiacos de Almeida [UNESP] (Univ Federal Uberlandia, 2015)
The enriched environment (EE) is a promoter of physical activity, by its characteristics such as ample room for movement and exploration, presence of wheels, tunnels and toys. The maintenance of animals in enriched environment can bring a range of benefits, but the majority of the researches investigate cognitive parameters and changes related to the nervous system. The aim of this study was to examine the effects of the maintenance of aged rats in enriched cages on biochemical and metric parameters. Wistar rats were randomly distributed (n=6) into two groups during 6 weeks: control (C) in a conventional cage and enriched environment (EE). The body mass were recorded weekly and the body length at the end of the study. After euthanasia, blood was collected for analysis of glucose, triglycerides and the brain was collected for analysis of mass. The EE group had higher brain mass and lower gain of body weight compared to control group. The control group animals had normal values of blood glucose and triglyceride levels, and the maintenance in an EE did not promote changes in these parameters. Therefore, it can be concluded that the EE group increases brain mass and reduces the gain of body weight without changing the blood glucose and triglycerides in aged animals.

O ambiente enriquecido (AE) pode ser considerado como promotor de atividade física, pelas suas características como um amplo espaço para deslocamento e exploração, a presença de rodas de atividade, túneis e brinquedos. A manutenção de animais em ambiente enriquecido pode proporcionar uma série de benefícios, mas grande parte dos estudos tem focado a investigação de parâmetros cognitivas e alterações relacionadas ao sistema nervoso. O objetivo deste estudo foi examinar os efeitos da manutenção de ratos idosos em gaiolas enriquecidas sobre parâmetros bioquímicos e métricas. Ratos Wistar foram distribuídos aleatoriamente ( n = 6) em dois grupos durante 6 semanas: controle (C) mantido em gaiola convencional e ambiente enriquecido (AE) . A massa corporal foi registrada semanalmente e o comprimento corporal ao final do estudo. Após a eutanásia, amostras de sangue foram coletadas para análise de glicose e triglicérides e o encéfalo foi coletado para registro da massa. O grupo AE apresentou maior massa encefálica e menor ganho de peso corporal, em comparação ao grupo controle. Os animais do grupo controle apresentaram valores normais de glicose e triglicerídeos no sangue e a manutenção no AE não promoveu alterações nestes parâmetros. Portanto, pode ser concluído que a manutenção no AE aumenta a massa encefálica e reduz o ganho de peso corporal sem alterar a glicose e triglicerídeos no sangue de animais idosos.
Efeitos do ambiente enriquecido em parametros bioquímicos e métricos de ratos idosos
Keywords: Enriched environment; Physical activity; Obesity; Brain mass; Ambiente enriquecido; Atividade física; Obesidade; Massa encefálica